ANALISIS PERMASALAHAN BANJIR DAN STRATEGI MITIGASI BENCANA BANJIR DI KABUPATEN KAMPAR PROVINSI RIAU - Febblina Daryanes; Irda Sayuti; Khusnul Fikri (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2026)
ANALYSIS OF FLOOD PROBLEMS AND FLOOD DISASTER MITIGATION STRATEGIES IN KAMPAR REGENCY, RIAU PROVINCE Kampar Regency in Riau Province is a flood-prone area where flood management efforts still require comprehensive improvement. Flood occurrences are influenced not only by natural factors but also by spatial planning, environmental management, and the roles of institutions and communities. This study aims to identify the causes of flooding, analyze mitigation efforts undertaken by the Regional Disaster Management Agency (RDMA) and local communities, and formulate appropriate strategies to reduce flood risk. The research was conducted in Sipungguk Village and Buluh Nipis Village, Kampar Regency, in May 2024 using a qualitative approach through observation, interviews, and documentation. The findings show that flooding is caused by prolonged high rainfall, lowland topography, overflow of the Kampar River influenced by the operation of the Koto Panjang Hydropower Reservoir, inadequate drainage systems, land-use change, and settlement development along riverbanks. Flood mitigation efforts by RDMA are still dominated by emergency response and short-term preparedness measures, including flood hazard mapping, evacuation, and community education, which have not significantly reduced flood risk. This study concludes that flood mitigation in Kampar Regency remains reactive and poorly integrated. Therefore, an integrated mitigation strategy is required, emphasizing institutional capacity strengthening, community-based risk management, environmental management, and coordination of water discharge regulation with the Koto Panjang Hydropower Plant.